2015
DOI: 10.1186/s12913-015-1220-6
|View full text |Cite
|
Sign up to set email alerts
|

Counselling practices in community pharmacies in Riyadh, Saudi Arabia: a cross-sectional study

Abstract: BackgroundCommunity pharmacists play a crucial role in optimising medication use and improving patient outcomes, whilst preventing medication misuse and reducing costs. Evidence suggests that pharmacists counselling improves clinical outcomes, quality of life, drug and disease knowledge and reduces health service utilisation. This study aims to investigate the counselling practices of community pharmacists in Riyadh, the capital of Saudi Arabia.MethodsThe study consisted of two parts: simulated patients (SPs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
134
5
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(156 citation statements)
references
References 21 publications
15
134
5
2
Order By: Relevance
“…While, for example, barely any information was provided for the criterion ‘side effects’, pharmacies often provided information about the dosage of the medication. Similar differences are also seen in the international literature 6, 7, 16, 28, 30, 31, 41, 42…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…While, for example, barely any information was provided for the criterion ‘side effects’, pharmacies often provided information about the dosage of the medication. Similar differences are also seen in the international literature 6, 7, 16, 28, 30, 31, 41, 42…”
Section: Discussionsupporting
confidence: 83%
“…Stiftung Warentest, a consumer organisation in Germany, also conducts test purchases at regular intervals and identifies a rather poor quality advisory service 8, 10. This is in no way a problem limited to Germany because such deficiencies in the advice provided in pharmacies are described many times in the international literature 23, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38. On the other hand, there are also a few examples internationally of in part appropriate advisory services provided by pharmacies 39, 40…”
Section: Discussionmentioning
confidence: 99%
“…A study done in Turkish Republic of Northern Cyprus revealed that only 73.7% of pharmacists gave dosing instructions to the simulated patients and only 5.9% of the simulated patients were warned by the pharmacists about potential drug and food interactions 15. Similar inconsistencies between self-reported practice of pharmacists and their actual dispensing practice measured using SPs were reported by another study done in Saudi Arabia 16. This discrepancy might be due to pharmacists’ provision of socially desirable responses in the questionnaire and perception of good dispensing practice.…”
Section: Discussionmentioning
confidence: 61%
“…In a study conducted in Saudi Arabia, being too busy was reported by over half of pharmacists (59.6%) as the barrier for patient counseling 16. However, those factors could not hold priority when checked with the actual situation observed by SP.…”
Section: Discussionmentioning
confidence: 99%
“…12 Moreover, these services contain a strong cognitive component, which requires the development of clinical reasoning, clinical decision-making and the evaluation of results. 15,16 Thus, defining dispensing work processes and related quality indicators are necessary to ensure the indication, effectiveness, safety and convenience of the use of medicines by patients. 14 However, in some countries, the absence of the medical history of patients in community pharmacies has been identified as a barrier to performing qualified dispensing.…”
Section: What Is K Nown and Objec Tivementioning
confidence: 99%